Pendampingan Penguatan Keterampilan Pemanfaatan Kain Perca pada Kader PKK Desa Suntenjaya Kecamatan Lembang Kabupaten Bandung Barat - Marlina Marlina; Pipin Tresna Prihatin; Astuti Astuti; Mila Karmila (Universitas Mathla'ul Anwar Banten, 2021)
ASSISTANCE FOR CADRE STRENGTHENING SKILLS UTILIZATION OF THE REMAINING CLOTH EMPOWERMENT OF FAMILY WELFARE IN SUNTENJAYA VILLAGE, LEMBANG DISTRICT, WEST BANDUNG REGENCY. Family welfare is a condition of a family that has resilience, strength, and ability to be able to live independently. As a manifestation of efforts to improve family welfare is through community empowerment efforts in the form of providing education and skills through the realization of a skills mentoring program for Family Welfare Empowerment cadres. One of the knowledge and skills that can be learned in an effort to empower rural communities is entrepreneurial knowledge and skills in making craft products with simple techniques. Assistance The skill of making craft products from scraps of cloth can be used as an effort to show his existence and can be used as a provision to open a family business to earn income so that it can help improve his family's welfare. The method used is in the form of skills strengthening mentoring. The implementation is to provide assistance in strengthening the skills to use fabric scraps to open a business for the manufacture of various craft products. The result of the skills strengthening mentoring activity was that the participants were able to make handicraft products to use leftover cloth using quiling and firing techniques. Each participant made handicrafts in the form of hangers and brooches. In this skill strengthening mentoring activity, the results of these products are generally good because the participants can apply the techniques given by the instructor, but there are still deficiencies in choosing the color combination that is not suitable because of the limited materials.